2022
DOI: 10.1021/acs.jctc.1c00792
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Electronic and Nuclear Motions during Azobenzene Photoisomerization Monitored by Ultrafast Electron Diffraction

Abstract: Ultrafast electron diffraction is a powerful technique that can resolve molecular structures with femtosecond and angstrom resolutions. We demonstrate theoretically how it can be used to monitor conical intersection dynamics in molecules. Specific contributions to the signal are identified which vanish in the absence of vibronic coherence and offer a direct window into conical intersection paths. A special focus is on hybrid scattering from nuclei and electrons, a process that is unique to electron (rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Our previous thoeretical work has demonstrated that the TRXD signals can potentially image transient electron transition densities directly associated with CI passages in azobenzene 49,50 , 4-thiouracil 29 , exhibiting characteristic positive/negative oscillations due to the formation of electronic coherences. We further had shown that the two-dimensional diffraction pattern, domi-nated by elastic scattering, can be used to monitor conformational changes e.g., cis to trans photoisomerization in azobenzene 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous thoeretical work has demonstrated that the TRXD signals can potentially image transient electron transition densities directly associated with CI passages in azobenzene 49,50 , 4-thiouracil 29 , exhibiting characteristic positive/negative oscillations due to the formation of electronic coherences. We further had shown that the two-dimensional diffraction pattern, domi-nated by elastic scattering, can be used to monitor conformational changes e.g., cis to trans photoisomerization in azobenzene 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the PES scan profiles, the standard mechanism of light-induced rotational isomerization in azobenzene 11 and its derivates 53 can be assumed also in this class of compounds. According to that, the E isomer is expected to absorb primarily the UV radiation thanks to the symmetrically allowed transition from ground singlet state to the second excited singlet state (S 2 ← S 0 , ππ*) transition and to much lower extent the visible blue light corresponding to symmetrically forbidden transition to first excited singlet state (S 1 ← S 0 , nπ*).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, some portion of molecules in S 1 state can be created also under UV radiation thanks to S 1 /S 2 conical intersection seam corresponding to bending across the CNN bending mode. 11 Inspection of orbitals in the state S 2 showed that its electronic configuration can be expressed as n 2 π 1 π* 1 for every molecule, i.e. the bond order between nitrogen atoms in the azo-group is diminished and allows torsional rotation of the –CNNC– link.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades, a variety of X-ray sources have been developed, ranging from synchrotron radiation to tabletop high-harmonic generation setups. These enable scientists to experimentally resolve not only nuclear dynamics, , but also electronic motion following photoinitiated processes. There are several different possibilities to study the dynamics and electronic coherence induced by CoIns using simulated spectra. , In experiments, attosecond transient absorption spectroscopy (ATAS) has been successfully applied to resolve coupled nuclear and electron dynamics with great spectral and temporal resolution. Theoretical simulations could show that these spectra can be used among other to determine the population of different states, investigate the nuclear dynamics, or follow the wavepacket dynamics at a CoIn . To describe the dynamics at CoIn a multiconfigurational treatment is necessary, whereas most key features have been demonstrated to be also qualitatively reproduced using computationally cheaper approaches like MOM/TDDFT (maximum overlap method time-dependent density functional theory), enabling the treatment of larger molecular systems .…”
Section: Introductionmentioning
confidence: 99%